Insentif Dan Kompetensi Sebagai Kunci Keunggulan Kinerja Karyawan - Sikumbang Muharmansyah; Sinuhaji Yose Andre; Siddik Ega (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study analyzes the influence of incentives and competence on employee performance at the Serdang Indah Mandiri Savings and Loan Cooperative (KSP) in Medan City. Using a quantitative approach with an explanatory survey design, the study involved 85 employees as respondents through a saturated sampling technique. Data were collected using a structured questionnaire with a Likert scale and analyzed using multiple linear regression with SPSS 29.0. The results showed that: (1) incentives had a positive and significant effect on employee performance with a t-count of 4.213 > t-table 1.96 (p <0.001); (2) competence had a positive and significant effect on employee performance with a t-count of 3.784 > t-table 1.96 (p <0.001); and (3) incentives and competence simultaneously had a significant effect on employee performance with an F-count of 37.487 > F-table 3.11 (p <0.001). The research model was able to explain 56.6% of the variation in employee performance (R² = 0.566).